Achieving the Demographic Dividend in the Arab Republic of Egypt : Choice, Not Destiny - El-Saharty, Sameh (ed.); Nassar, Heba (ed.); Shawky, Sherine (ed.); Elshalakani, Amr (ed.); Hamza, Mariam M. (ed.); Zhang, Yi (ed.); Zeitoun, Nahla (ed.) (Washington, DC : World Bank, 2022)
The Arab Republic of Egypt was well on the path to achieving its demographic dividend at the turn of this century but has gone off track due to a reversal in its earlier fertility decline.